STUDY AND PREVENTION OF PROBLEMS OF CULTIVATED LAND AREAS - Yusupov Ibragim Mirsaydaliyevich (Galaxy International Interdisciplinary Research Journal, 2022)
Problems of the soil environment of arable land the creation and use of organic fertilizers in the fight against it, methods used in determining the degree of mineralization of arable land before mineralization in the soil haydov layer and neutralization of toxic chemicals.